Mechanical Properties of cold-drawn low carbon steel for nail manufacture: experimental observation (2013)
"The objective of this study is to investigate the influence of service situation on the mechanical properties of plain nails manufactured from low carbon steel. The influence of the degree of cold drawing on the mechanical properties and strain hardening of the material is investigated by tensile test experimentation. The stress-strain relationships of the cold-drawn low carbon steel were investigated over the 20, 25, 40 and 55% degree of drawn deformation for the manufacture of 4, 3, 2½ and 2 inches nails, respectively. The true stress-strain curves were analyzed to obtain the yield strength and tensile strength of the cold drawn steel. It is shown that the yield strength, tensile strength, hardness and toughness of the low carbon steel reduce with increasing degree of cold-drawn deformation. The micrographs of the deformed samples obtained using optical microscope shows that the grain structure elongates in the direction of the drawing operation and misorientation of the grains set in at 40 and 55% degree of deformation. The difference in yield strength was attributed to the strain hardening, resulting from the different degrees of drawn deformation."